AI- Assisted scaffolding: AI Implementation in English Speaking Communication - Ni Martarini; Agus Iswara; I Wahyudi (Penerbit Jurnal Indonesia, 2025)
This study investigates the impact of integrating Artificial Intelligence (AI) into a Project-Based Learning (PjBL) model to enhance students’ English speaking skills. Recognizing the persistent challenges in providing sufficient speaking practice opportunities in conventional classrooms, this research employed AI-based applications, including Character AI, TikTok, and video editing tools, to create an interactive and personalized speaking environment. This study examines the integration of Artificial Intelligence (AI) into a Project-Based Learning (PjBL) model to enhance students’ English speaking skills. The research was motivated by the limited opportunities for speaking practice in conventional classrooms. AI-based applications such as Character AI, TikTok, and video editing tools were employed to create an interactive and personalized learning environment. A total of 60 students participated in the study, divided into a control group applying conventional PjBL and an experimental group applying AI-assisted PjBLThe study involved 60 students divided into two groups: a control group applying conventional PjBL and an experimental group using AI-assisted PjBL. Data were collected through pre- and post-tests and analyzed using SPSS with descriptive statistics, normality testing, and independent samples t-test. The results revealed that the AI-assisted PjBL group achieved a higher mean speaking score (M = 82.00, SD = 6.103) compared to the control group (M = 72.00, SD = 5.038), with a statistically significant difference (t = 6.922, p < 0.05). These findings indicate that integrating AI in PjBL can significantly improve students’ speaking performance by providing adaptive feedback, increasing learner autonomy, and creating more authentic speaking practice opportunities. However, the study also highlights limitations, including restricted AI platforms and a relatively short experiment duration. The findings suggest that AI-assisted PjBL is a promising approach for enhancing speaking skills in higher education, but it should be complemented with extended practice and teacher facilitation to achieve optimal outcomes.